PENINGKATAN KUALITAS PELAYANAN JASA PADA DEPARTEMEN UMUM DAN LOGISTIK MELALUI PENDEKATAN INTERGRASI METODE SERVQUAL SIX SIGMA PT. Slena Cahaya Gemilang Surabaya - angga fadia nokta (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
This research aims to determine and analyze how much influence the quality of service to the level of satisfaction felt by customers who use services of EMKL PT. Slena Cahaya Gemilang. The model used in this research are the method of observation, interviews, questionnaires, and literature study using a Linkert scale and method of determination of the sample used was accidental sampling of as many as 100 samples. The method of analysis were used multiple linear regression methods. The results showed that the quality of service which consists of Realibility (X1), Responsiveness (X2), Assurance (X3), Emphaty (X4) and Tangible (X5) together have a positive influence. Where the regression equation Y = 0,165 X1 + 0,213 X2 + 0,256 X3 + 0,189 X4 + 0,228 X5. In addition, the F test found that service quality has a significant effect on customer satisfaction with a significance level of 0.000 or 0%.